Peran Laminar Air Flow Cabinet Dalam Uji Mikroorganisme Bagi Mahasiswa Tugas Akhir Di Laboratorium Biokimia - Harjanto, Sri; Raharjo, R (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Work safety and security in the laboratory environment is very much needed, especially those related to microorganisms. In this case the purpose of the survey is to find out what percentage of the success rate of inoculation or the planting of microorganisms using the Laminar Air Flow instrument. As for the method used based on the classification survey of the number of tools used. And from the observation / survey that the number of users of laminar water flow in the Biochemistry laboratory for 1 year (2017) shows a very significant number especially in certain months such as October - November reached 27, 31 users, overall the number of users was quite large. This means that the instrument is needed for its existence. Also from the types of activities carried out by the Final Project students so far by using these instruments can be well served means that the tool is able to help solve problems of students who are completing their research.